A new behavioral test for detecting decline of age-related cognitive ability in dogs - Nagasawa, Miho; Yatsuzuka, Aiko; Mogi, Kazutaka; Kikusui, Takefumi (Journal of veterinary behavior, 2012)
A simple test for detecting decline of cognitive ability in aged dogs is needed in modern society. We used a basic place-selection test to develop a new test to assess cognitive ability in dogs, using 25 house dogs. Three covered bowls were placed in front of the subject. One of them was the correct bowl, from which the subject was rewarded with a food treat when he/she chose it. If the subject made an incorrect selection, he/she was returned to the starting point and the trial was repeated. Cognitive ability was assessed by the number of errors needed to fulfill the criterion. We found a significantly high correlation between the dogs’ ages and the number of error trials, suggesting that age-related cognitive dysfunction may reliably be assessed by the documented place-learning test.